2004
DOI: 10.1292/jvms.66.585
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Enterohemorrhagic Escherichia coli (EHEC) O157 from Cattle in Selected Regions of Japan

Abstract: ABSTRACT. The prevalence of enterohemorrhagic Escherichia coli (EHEC) O157 was examined in bovine faeces. EHEC O157 was isolated from the faeces of 42 (13.0%) of 324 cattle. Of the 4 farms and the facilities tested, the 3 farms and the facilities wer e found positive for EHEC O157. The highest isolation rate among the farms was 33.7%. The prevalence of EHEC O157 in heifers was higher than that in calves and other cattle. No cattle positive for EHEC O157 showed any clinical signs except 2 calves with diarrhea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
(24 reference statements)
2
15
0
Order By: Relevance
“…However, under the assumption that the STEC and p-O157 potential pathogenic classes adopted in this study can be taken as a whole-sample proxy for the presence of STEC and O157 strains, the prevalence ranges here reported are consistent with the wide range of STEC prevalence (0.17 to 40%) observed in fecal samples from adult dairy cows in the United States (8,30,33,40,(61)(62)(63). These figures are also consistent with the range of STEC prevalence in dairy cattle observed in other countries (13,30,39,64). Also, E. coli strain O157:H7 has been frequently isolated in dairy herds in the United States (34)(35)(36)58) and in other countries (14,39,65).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, under the assumption that the STEC and p-O157 potential pathogenic classes adopted in this study can be taken as a whole-sample proxy for the presence of STEC and O157 strains, the prevalence ranges here reported are consistent with the wide range of STEC prevalence (0.17 to 40%) observed in fecal samples from adult dairy cows in the United States (8,30,33,40,(61)(62)(63). These figures are also consistent with the range of STEC prevalence in dairy cattle observed in other countries (13,30,39,64). Also, E. coli strain O157:H7 has been frequently isolated in dairy herds in the United States (34)(35)(36)58) and in other countries (14,39,65).…”
Section: Discussionsupporting
confidence: 87%
“…These figures are also consistent with the range of STEC prevalence in dairy cattle observed in other countries (13,30,39,64). Also, E. coli strain O157:H7 has been frequently isolated in dairy herds in the United States (34)(35)(36)58) and in other countries (14,39,65). It is known that young cattle harbor STEC at significant prevalence, often higher than that in adult cows (13,60,63,(65)(66)(67).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hancock et al (22) believe that heifers carried a significant amount of EHEC O157:H7 (CFU/g), compared to other categories of cattle. Ezawa et al (34) outlined that the overall prevalence of EHEC O157:H7 among cattle in Japan (5-10%), but that heifers exhibited higher rates (32-46%). In Italy, a prevalence of 16% among cows was reported (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is little information from long-term studies on the prevalence of EHEC O157 on farms. We previously reported that a remarkably high isolation rate was found on a farm that raised heifers [8].…”
Section: Shiga Toxin (Stx)-producing Escherichia Coli (Stec) Ismentioning
confidence: 98%